High School Transfer Students and the Transition to College: Timing and the Structure of the School Year. (January 2013) - Sutton, April; Muller, Chandra; Langenkamp, Amy G.
The timing of a high school transfer may shape students' transitions to college through its (mis)alignment with the structure of the school year. A transfer that occurs during the summer interrupts the four-year high school career, whereas a transfer that occurs midyear disrupts both the four-year high school career and the structure of the school year. Using the Education Longitudinal Study of 2002 (ELS), the investigators find that the penalty suffered after the transfer depends on the degree to which students' high school pathways synchronize with the curricular and extracurricular structure of the school year. Midyear transfer students appear to suffer the greatest postsecondary matriculation penalty. Students who transfer midyear are less likely to attend a four-year college compared with nontransfer and summer transfer students, whereas summer transfer students are less likely to attend a highly selective four-year college compared with their nontransfer counterparts. Curricular and extracurricular disruptions that transfer students experience after their school move explain some, but not all, of the negative associations observed between transferring and the transition to college. Directions for future research and the theoretical and policy implications of the results are discussed.